Production and purification of xylanase from alkaliphilic Bacillus licheniformis and its pretreatment of eucalyptus kraft pulp. (July 2018) - Raj, Abhay; Kumar, Sharad; Singh, Sudheer Kumar; Prakash, Jyoti
Abstract: Xylanases from bacterial sources have potential applications in various industrial processes. In the present study, the effect of enzymatic pre-treatment on pulp bleaching has been investigated using purified xylanase from alkaliphilic Bacillus licheniformis strain Alk-1. The xylanase produced by present isolate while growing on wheat bran was purified to homogeneity by 5.84-fold purification with 15.97% recovery by anion exchange chromatography using DEAE-cellulose. The estimated molecular weight of the xylanase was 46 kDa. The optimal pH and temperature for xylanase activity were pH 9.0 and 60 °C, respectively. The enzyme showed good activity retention (80%) after 1 h incubation at 60 °C and pH 9.0. Enzyme activity was stimulated by Ca 2+, Fe 2+ and Mg 2+ and inhibited by Cd 2+, Hg 2+ and Cu 2+ at 2 mM and 10 mM conc. For xylan, the enzyme gave a Km value of 5.26 mg/mL and Vmax value of 433 μM/min/mg proteins when the reaction was carried out at 60 °Cand pH 9.0. Pre-treatment of kraft pulp with xylanase showed 19% reduction in kappa number, compared to control pulp, after 2 h treatment. The SEM and FTIR analysis of xylanase-treated pulp revealed significant morphological and structural changes on pulp fibres. GC-MS analysis of filtrates from control and xylanase-treated pulps showed variation in the presence of different plant-derived organic compounds. The present work finds potential application in paper production by making it cleaner and ecofriendly process. Highlights: An alkaline xylanase was purified from alkaliphilic Bacillus licheniformis. The MW of purified xylanase was 46 kDa on SDS-PAGE. Xylanase showed optimum activity at pH 9.0 and 60 °C. Pretreatment of kraft pulp with xylanase led to reduced in kappa no. by 19%.